A war to be won fighting the Second World War - Murray, Williamson; Millett, Allan Reed. (Cambridge, MA : Belknap Press of Harvard University Press, 2000)
In the course of the twentieth century, no war looms as profoundly transformative or as destructive as World War II. Its global scope and human toll reveal the true face of modern, industrialized warfare. Now, for the first time, we have a comprehensive, single-volume account of how and why this global conflict evolved as it did. A War To Be Won is a unique and powerful operational history of the Second World War that tells the full story of battle on land, on sea, and in the air. Williamson Murray and Allan R. Millett analyze the operations and tactics that defined the conduct of the war in both the European and Pacific Theaters. Moving between the war room and the battlefield, we see how strategies were crafted and revised, and how the multitudes of combat troops struggled to discharge their orders. The authors present incisive portraits of the military leaders, on both sides of the struggle, demonstrating the ambiguities they faced, the opportunities they took, and those they missed. Throughout, we see the relationship between the actual operations of the war and their political and moral implications. A War To Be Won is the culmination of decades of research by two of America's premier military historians. It avoids a celebratory view of the war but preserves a profound respect for the problems the Allies faced and overcame as well as a realistic assessment of the Axis accomplishments and failures. It is the essential military history of World War II-from the Sino-Japanese War in 1937 to the surrender of Japan in 1945-for students, scholars, and general readers alike.
Frontmatter -- PREFACE -- CONTENTS -- MAPS -- 1 Origins of a Catastrophe -- 2 The Revolution in Military Operations, 1919-1939 -- 3 German Designs, 1939-1940 -- 4 Germany Triumphant, 1940 -- 5 Diversions in the Mediterranean and Balkans, 1940-1941 -- 6 Barbarossa, 1941 -- 7 The Origins of the Asia-Pacific War, 1919-1941 -- 8 The Japanese War of Conquest, 1941-1942 -- 9 The Asia-Pacific War, 1942-1944 -- 10 The Battle of the Atlantic, 1939-1943 -- 11 Year of Decision for Germany, 1942 -- 12 The Combined Bomber Offensive, 1941-1945 -- 13 The Destruction of Japanese Naval Power, 1943-1944 -- 14 The Killing Time, 1943-1944 -- 15 The Invasion of France, 1944 -- 16 The End in Europe, 1944-1945 -- 17 The Destruction of the Japanese Empire, 1944-1945 -- 18 The End of the Asia-Pacific War, 1945 -- 19 Peoples at War, 1937-1945 -- 20 The Aftermath of War -- Epilogue: In Retrospect -- Appendixes: -- Notes -- Suggested Reading -- Acknowledgments -- Illustration Credits -- Index
Description based upon print version of record.
Includes bibliographical references (p. 613-637) and index.
George E. Bishop Memorial.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
English.
Keywords: 1900-1999; World War, 1939-1945.; History, Modern -- 20th century; Guerre mondiale, 1939-1945.; Histoire; 15.50 general world history; history of great parts of the world, peoples, civilizations: general; History, Modern; Tweede Wereldoorlog; Oorlogvoering; 2; World War, 1939-1945.